PENGARUH INFLUENCER MARKETING, ONLINE CUSTOMER REVIEW DAN LIVE STREAMING SHOPPING TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK DI TIKTOK SHOP - Nayla Auroravita; Muchammad Agung Miftahuddin; Irawan Randikaparsa; Tri Septin Muji Rahayu; Ika Yustina Rahmawati (LPPM STIE Muhammadiah Bandung, 2026)
The dynamics of information technology advances have encouraged changes in consumer behavior, especially in online shopping activities through social media such as TikTok Shop. The purpose of this study is to examine the application of influencer marketing, online customer reviews, and live streaming shopping in influencing the purchase decision of cosmetic products in students in the city of Purwokerto. This research is based on the increasing intensity of online shopping activities through social media on changes in consumer behavior towards the purchase decision-making process. Quantitative with a causal approach was used as the basis of the research, involving 127 respondents selected by purposive sampling using non-probability sampling techniques, then given questionnaires as a source of research data, analyzed using SPSS software version 27. The findings of the study indicate that influencer marketing, online customer reviews, and live streaming shopping simultaneously have a positive and significant effect on purchase decisions and contribute to increasing consumer confidence and interest in buying cosmetic products in students in the city of Purwokerto who shop through TikTok Shop.